2010
DOI: 10.1073/pnas.0911838107
|View full text |Cite
|
Sign up to set email alerts
|

Transventricular delivery of Sonic hedgehog is essential to cerebellar ventricular zone development

Abstract: Cerebellar neurons are generated from two germinal neuroepithelia: the ventricular zone (VZ) and rhombic lip. Signaling mechanisms that maintain the proliferative capacity of VZ resident progenitors remain elusive. We reveal that Sonic hedgehog (Shh) signaling is active in the cerebellar VZ and essential to radial glial cell proliferation and expansion of GABAergic interneurons. We demonstrate that the cerebellum is not the source of Shh that signals to the early VZ, and suggest a transventricular path for Shh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 36 publications
11
156
2
2
Order By: Relevance
“…Although we were not able to detect the expression of SHH in PCs before 17 gw, we observed that GCPs expressed GLI1 at all stages analyzed (Fig. 3B), suggesting that an additional source of SHH might exist before 17 gw (32,33). However, SHH mRNA expression detected in the PCs from 17 gw coincides with a peak in GCP proliferation (Figs.…”
Section: Gcp Proliferation Is Similar In Cerebellar Vermis and Hemispmentioning
confidence: 44%
“…Although we were not able to detect the expression of SHH in PCs before 17 gw, we observed that GCPs expressed GLI1 at all stages analyzed (Fig. 3B), suggesting that an additional source of SHH might exist before 17 gw (32,33). However, SHH mRNA expression detected in the PCs from 17 gw coincides with a peak in GCP proliferation (Figs.…”
Section: Gcp Proliferation Is Similar In Cerebellar Vermis and Hemispmentioning
confidence: 44%
“…Decreasing hydrostatic pressure results in smaller brain ventricles, and smaller and disorganized neural tissue [63]. Factors within the embryonic CSF, including sonic hedgehog and choroid plexus-derived insulin-like growth factor 2, promote the proliferation of neural progenitors [59,78,90,170]. The CSF effect is optimal when age-matched CSF and tissue are combined, highlighting the dynamic nature of both the choroid plexus/CSF axis and of the intrinsic state of the responding cells [18,78].…”
Section: Embryonic and Postnatal Developmentmentioning
confidence: 99%
“…essential to regulate the proliferation of radial glia and, consequently, the expansion of GABAergic interneurons [98]. In this case, however, endogenous PCs are not the source of Shh ligand, which is secreted by the choroid plexi and transventricularly delivered by the embryonic cerebrospinal fluid [98].…”
Section: Shh and Gabaergic Interneuronsmentioning
confidence: 99%
“…This morphogen, secreted by Purkinje cells from E17.5 [95][96][97] and by choroid plexi at earlier time points [98], controls the production of appropriate numbers of excitatory and inhibitory interneurons (Fig. 2).…”
Section: Cerebellar Territory and Germinal Zonesmentioning
confidence: 99%